PENGARUH PENGGUNAAN METODE NUMBERED HEAD TOGETHER (NHT) BERBANTU PETA KONSEP TERHADAP HASIL BELAJAR IPS TERPADU SISWA KELAS VIII SEMESTER GENAP MTs NEGERI 1 LAMPUNG TIMUR - Gus Muchrozin; Triani Ratnawuri (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2017)
Students have low graduation rate on KKM replicate mid semester IPS Integrated makes the need for research in class VIII C MTs Negeri 1 Lampung Timur. With various elements that support the learning process then students should be able to learn well. This provides the discourse that with various elements for learning fulfilled it can affect the mastery of concepts and improve student learning outcomes, and use the method of Numbered Head Together (NHT) aided concept map selected by the author because it is appropriate for this problem. The formulation of this research problem is "is there any effect of the use of head together method (NHT) assisted concept map of integrated IPS learning outcomes grade VIII students even semester of MTs Negeri 1 Lampung Timur academic Year 2016/2017?”The purpose of this research is "To know the effect of using method of Numbered Heads Together (NHT) assisted concept map to the result of study of IPS integrated Grade VIII grade students of MTs Negeri 1 Lampung Timur in academic year 2016/2017".This research is quantitative to find out how the influence of the method of Numbered Head Together (NHT) assisted Concept Map on Integrated IPS learning results, using Quasi Experiment Design. In the test using Simple Linear Regression formula Y'= 45,17074 + 0,5237 X then from the analysis results obtained that there is a positive influence. This is evidenced by the calculation of the analysis that t_count> t_table and seen at a significant level of 5% is 7.04> 1.70, thus the hypothesis is accepted. So "there is a positive influence using the method of Numbered Head Together (NHT) on the learning outcomes IPS Integrated VIII class students even semester MTs Negeri 1 Lampung Timur academic 2016/2017